Remote Teaching's Legacy Perceptions: An Interview Study with Brazilian Education Professionals - Lima, Mayka de S.; David, José Maria N.; Maciel, Rita Suzana P. (Anais do Simpósio Brasileiro de Informática na Educação (SBIE), 2024)
Remote teaching has provided a range of experiences for education professionals. Likewise, this study presents a comprehensive discussion from semi-structured interviews about these educational experiences through a postpandemic lens. Interviews assist in acquiring memories by focusing on specific aspects, such as perceptions of teaching practices, technological difficulties, and vital functionalities for remote teaching. The study used qualitative methods to dissect the responses of 25 education professionals at different levels of education. As a result, we obtained a comprehensive understanding of the professionals’ individual experiences, indicating the importance of integrating pedagogical resources and strategies into educational practices.